Expressive language in children with Kabuki syndrome - Defloor, Truus; van Borsel, John; Schrander-Stumpel, Constance T.R.M.; Curfs, Leopold M.G. (American journal of medical genetics. Part A, 2005)
Since the description of Kabuki syndrome in 1981 over 300 cases from a variety of countries have been reported. Only a limited number of these reports, however, provided data on speech language development. Ghent University Hospital (J. Van Borsel, T. Defloor) and the Department of Clinical Genetics, Academic Hospital Maastricht (C.T.R.M. Schrander‐Stumpel, L.M.G. Curfs) are directing research on the specific nature of communicative development in persons with Kabuki syndrome. The aim of the present study was to delineate the language difficulties in the syndrome. The subjects were six Dutch‐speaking children (three male, three female), with chronological age ranging from 4.4 to 10.6 years (mean = 8.1). Spontaneous speech samples were collected, subjected to a consensus orthographic transcription, and analyzed by means of TOAST [Moerman‐Coetsier and Van Besien, 1987], a Dutch standardized diagnostic instrument to investigate different aspects of spontaneous language production. In all the children, expressive language abilities were impaired. Poor morphosyntactic abilities were consistently demonstrated. Lexical and pragmatic difficulties were also present, whereas phonological development was less often affected. © 2004 Wiley‐Liss, Inc.